Industrial solid waste-based ultrafine powder and preparation method and application thereof

By co-grinding industrial solid waste with NaOH fine powder and performing high-temperature calcination, low-temperature aging and hydrothermal reaction, industrial solid waste-based ultrafine powder with high specific surface area and porous structure was prepared, which solved the problem that existing processes were difficult to improve powder performance at the same time, and significantly improved its performance in low-carbon gelled materials or ground polymers.

CN119750928APending Publication Date: 2025-04-04ENERGY & ENVIRONMENT RES INST OF HEILONGJIANG PROVINCE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411942204.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

It is difficult for existing processes to simultaneously increase the specific surface area of ​​industrial solid waste-based ultrafine powder, reduce the particle size, form a rough porous structure, and enhance the mass and heat transfer of the reaction system.

Method used

After co-grinding the industrial solid waste with NaOH fine powder, high-temperature roasting, grinding, low-temperature aging and hydrothermal reaction, industrial solid waste-based ultrafine powder with a large specific surface area, porous structure and good dispersion properties were prepared.

Benefits of technology

The specific surface area and microporous area of ​​industrial solid waste-based ultrafine powder are significantly improved, the particle size is reduced, and the rough porous structure is formed, which enhances its performance in low-carbon gelling materials or ground polymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005212782210000011
    Figure HDA0005212782210000011
Patent Text Reader

Abstract

The present invention provides an industrial solid waste-based ultrafine powder, which is obtained by grinding particles or powder of industrial solid waste with NaOH fine powder, and then performing high-temperature roasting, grinding, low-temperature aging and hydrothermal reaction in sequence; the industrial solid waste is a mixture of any one or two of calcined activated graphite tailings or coal gangue, and its SiO2 content is 35% to 65%, and the content ratio of SiO2 to Al2O3 is between 2-5; the weight ratio of sodium hydroxide fine powder and particles or powder of industrial solid waste is 0.6 to 2.0:1; high-temperature roasting is roasting at 650°C to 750°C for 2h to 4h. The present invention also provides a method for preparing the ultrafine powder. The method of the present invention can change the smooth and dense structure of graphite tailings or coal gangue, significantly increase its specific surface area, reduce the particle size, and form a rough porous structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an industrial solid waste-based ultrafine powder, in particular to an ultrafine powder additive used in a low-carbon gelling material, and a preparation method thereof, and belongs to the field of solid waste resource utilization. Background Art

[0002] Graphite tailings are a type of industrial solid waste discharged during the graphite beneficiation and impurity removal process. According to statistics, in the flotation mining process, 10-15 tons of graphite tailings can be produced for every ton of graphite purified. With the booming graphite market, the discharge of graphite tailings has increased significantly in the past decade. Coal gangue is also a type of industrial solid waste. It is a black-gray rock with a low carbon content and harder than coal that is discharged during coal mining and coal washing. If this type of industrial solid waste is not properly handled, it will cause serious harm to the ecological environment such as soil, water, and atmosphere. There is also a risk of geological disasters, and it will also cause waste of resources.

[0003] From the perspective of chemical composition, graphite tailings and coal gangue mainly contain metal oxides such as SiO2, Al2O3 and Fe2O3, among which the SiO2 content is about 58% to 64%, which is similar to fly ash. From the perspective of mineral phase structure, graphite tailings mainly contain quartz phase, plagioclase, mica and hematite, and coal gangue mainly contains quartz, kaolinite and muscovite. Therefore, it has the potential to replace siliceous raw materials in the field of building materials (such as low-carbon cementitious materials, geopolymers, moisture-proof, anti-corrosion and flame-retardant materials, etc.). However, the volcanic ash activity of plagioclase and quartz phases is relatively low, and it is necessary to use certain technical means and process methods to effectively stimulate its activity.

[0004] Using abandoned industrial solid waste as a source of silicon and aluminum to prepare ultrafine powders is an important new way to realize its resource utilization and has good development prospects. Ultrafine mineral powders have advantages such as good dispersibility, filling pore structure, strengthening system mass transfer and heat transfer, and promoting boundary nucleation and precursor growth. For example, adding mineral powders to the preparation process of low-carbon cementitious materials, geopolymers, moisture-proof, anti-corrosion and flame-retardant materials can help increase the specific surface area of ​​particles in the reactant system, improve the solubility and volcanic ash activity of silicon and aluminum components in the raw materials, and make it easier to convert raw materials into efficient aluminosilicate materials, thereby promoting the polymerization reaction process of low-carbon cementitious materials or geopolymers and enhancing their matrix structure.

[0005] The preparation methods of ultrafine powder mainly include pulverization and synthesis. The pulverization method is to ultrafine the raw materials through physical means such as mechanical grinding or airflow grinding. It does not involve chemical reactions, has more chemical reaction activity stimulation effects, and does not have the function of modifying the microscopic morphology and structure. The synthesis method is to form micro-nano particles by nucleating and growing the material through chemical reactions, which is suitable for preparing ultrafine powders with specific structures and functions. Ming Yang and others from the Guangxi Industrial Waste Slag Building Materials Resource Utilization Engineering Technology Research Center used an ultrafine vibration grinder to grind and mix slag, steel slag, manganese slag, and fly ash to prepare ultrafine concrete admixtures. Ultrafine grinding can significantly stimulate the activity of water-quenched manganese slag, but the activity stimulation effect on steel slag is weak. Ultrafine grinding has a grinding effect on solid waste particles, making most of the particles tend to be smooth, but the particles after grinding do not have the characteristics of rough and porous structures. Although the specific surface area has increased, the solubility and volcanic ash activity of the silicon and aluminum components are low. Du Kaimin et al. used hydrothermal synthesis to convert desulfurized gypsum into ultrafine powdered calcium carbonate. The particles after the reaction showed a certain agglomeration phenomenon. The particles were cubic in shape and below 10 μm, and did not show the characteristics of a porous structure. Li Leilei et al. put the regenerated micro powder into a vibration mill, changed the vibration mill filling rate (35%, 40%, 45%, 50%, 55%, 60%), and the material-ball ratio (1:8, 1:10, 1:12, 1:14), and after obtaining the optimal grinding parameters, they also carried out ultrafine grinding of mineral powder and water glass old sand. The obtained ultrafine powder D 50 7.22~9.07μm, D 99 The particle size of the particles is 33.92-41.37 μm, which means that although the specific surface area has been improved, the particle size corresponding to the cumulative distribution percentage of 99% is greater than 30 μm. Therefore, it is difficult to achieve the goals of increasing the specific surface area, reducing the particle size, forming a rough porous structure, and enhancing the mass and heat transfer of the reaction system at the same time in the existing process, whether it is physical treatment or chemical treatment. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing industrial solid waste-based ultrafine powder, so that it can obtain a larger specific surface area, a porous structure and better dispersion performance through a chemical ultrafine treatment process, and is suitable for preparing low-carbon gelling materials or geopolymers with better performance.

[0007] The technical solution of the present invention is as follows:

[0008] In a first aspect, the present invention provides an industrial solid waste-based ultrafine powder, which is obtained by grinding industrial solid waste particles or powder with NaOH fine powder, and then performing high-temperature roasting, grinding, low-temperature aging and hydrothermal reaction in sequence;

[0009] The industrial solid waste has a SiO2 content of 35% to 65%, and a SiO2 to Al2O3 content ratio of 2-5; preferably, the industrial solid waste is any one of calcined activated graphite tailings or coal gangue, or a mixture of the two.

[0010] The microscopic morphology of the industrial solid waste-based ultrafine powder described in the present invention includes various forms, such as any one or a combination of two or more of spherical, spherical, cubic, etc.

[0011] More than 90% of the particles in the industrial solid waste-based ultrafine powder of the present invention have a particle size of no more than 20 μm; the micropore area is no less than 30 m 2 / g; specific surface area not less than 19m 2 / g.

[0012] In a second aspect, the present invention also provides a method for preparing the industrial solid waste-based ultrafine powder according to the first aspect, comprising the following steps:

[0013] 1) Alkali melting

[0014] Grind the fine powder of sodium hydroxide (NaOH) and the particles or powder of industrial solid waste until they are completely mixed and then calcine at high temperature;

[0015] The industrial solid waste has a SiO2 content of 35% to 65%, and a SiO2 to Al2O3 content ratio of 2 to 5; preferably, the industrial solid waste is calcined activated graphite tailings or coal gangue, or a mixture of the two;

[0016] The weight ratio of the sodium hydroxide fine powder to the particles or powder of industrial solid waste is preferably 0.6 to 2.0:1;

[0017] The high temperature calcination treatment preferably has a calcination temperature of 650°C to 750°C and a calcination time of 2h to 4h;

[0018] 2) Aging

[0019] The solid after alkali fusion treatment in step 1) is mixed with sodium silicate in a weight ratio of 1:0.30-0.80 and ground into powder, and then water is added at a solid-liquid ratio of 6-12 mL / g, first aged at 50-80° C. for 1 h to 3 h, and then aged at room temperature for 12 h to 16 h to obtain a precursor for a hydrothermal reaction;

[0020] 3) Hydrothermal reaction

[0021] The precursor obtained in step 2) is subjected to a hydrothermal reaction at 95° C. to 110° C. for 7 h to 9 h, and then cooled, filtered and dried to obtain an industrial solid waste-based ultrafine powder.

[0022] In the preparation method described in the present invention, the alkali during alkali fusion plays an important role in the transformation of the mineral phase structure of graphite tailings or coal gangue. First, it controls the state of silicate ionization during the synthesis of ultrafine powders, and transforms the stable mineral phase structure into an amorphous soluble state; second, it participates in the polycondensation reaction of silicate ions and aluminate ions, accelerates the subsequent hydrothermal reaction rate, and shortens the reaction time. The inventors have found through experiments that based on the process framework described in the present invention, when other process conditions in the above-mentioned synthesis process remain unchanged, ultrafine powders of different particle sizes can be synthesized by only changing the alkali-solid ratio of the alkali fusion process. Therefore, in a more preferred embodiment of the present invention, the microscopic morphology and particle size of the ultrafine powder finally obtained are controlled by adjusting the weight ratio of graphite tailings or coal gangue to NaOH particles in the alkali fusion treatment, and the weight ratio of the alkali fusion powder and sodium silicate.

[0023] In a third aspect, the present invention further provides the use of the industrial solid waste-based ultrafine powder described in the first aspect in the preparation of low-carbon cementitious materials.

[0024] The low-carbon cementitious material is an inorganic cementitious material with a three-dimensional network structure composed of AlO4 and SiO4 tetrahedral structural units, which is prepared by replacing part of the cement with fly ash and graphite tailings under the action of an alkali activator at normal temperature and pressure.

[0025] The industrial solid waste-based ultrafine powder can be used as a functional additive in the preparation of the low-carbon gelling material. In a preferred embodiment, the industrial solid waste-based ultrafine powder is used in the preparation of the alkali-activated gelling material in an addition amount of 8-10%.

[0026] Compared with the prior art, the method of the present invention can change the smooth and dense structure of graphite tailings or coal gangue, significantly increase its specific surface area, reduce the particle size, and form a rough porous structure. This plays a key role in uniforming the particle size structure of the system and enhancing the reaction mass transfer and heat transfer of the system for the subsequent preparation of low-carbon gelling materials or geopolymers with better mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a process flow chart of a specific embodiment of the present invention.

[0028] Figure 2A This is the microscopic morphology of graphite tailings.

[0029] Figure 2B This is a microscopic morphology of coal gangue.

[0030] Figure 3 This is a microscopic morphology of the scaly spherical ultrafine powder obtained in Example 1.

[0031] Figure 4 This is a microscopic morphology of the spherical and cubic blended ultrafine powders obtained in Example 2.

[0032] Figure 5 This is a microscopic morphology of the spherical ultrafine powder with a particle size of less than 1 μm obtained in Example 3.

[0033] Figure 6 This is a microscopic morphology of the ultrafine powder prepared by the method of comparative example 1.

[0034] Figure 7 This is a microscopic morphology of the ultrafine powder prepared by the method of Comparative Example 2. DETAILED DESCRIPTION

[0035] The present invention provides an industrial solid waste-based ultrafine powder and a preparation method thereof, such as Figure 1 As shown, the preparation method comprises the following steps in the specific implementation process:

[0036] 1) Activation pretreatment of solid waste

[0037] Use a crusher to crush the blocky gangue into particles and pass through a 100-mesh sieve to obtain powdered gangue. Place the powdered gangue in a drying oven and dry it at 105°C for 3 hours. Then, pre-calcine the dried gangue at 750°C for 2 hours.

[0038] 2) Alkali melting treatment of solid waste

[0039] Firstly, the sodium hydroxide (NaOH) particles are ground into fine powder, then a certain amount of industrial solid waste after roasting and activation is taken, and the mixture is ground and mixed with the NaOH fine powder, and then roasted at high temperature;

[0040] 3) Aging treatment

[0041] The solid obtained after the alkali melting treatment in step 2) is mixed with a certain mass of sodium silicate and ground into powder, and then water is added according to a certain solid-liquid ratio and stirred sufficiently, and low-temperature aging treatment is performed to obtain a precursor for a hydrothermal reaction;

[0042] 4) Hydrothermal reaction

[0043] The precursor obtained in step 3) is subjected to a hydrothermal reaction in a stainless steel reactor. After the reaction is completed, the precursor is taken out and cooled to room temperature, filtered and separated, and the water is dried to obtain graphite tailings or coal gangue-based ultrafine powder.

[0044] In the scheme of the present invention, the industrial solid waste described in step 2) is preferably any one or a combination of two or more of calcined and activated graphite tailings or coal gangue particles or powders.

[0045] The graphite tailings are preferably graphite tailings produced in Luobei County, Hegang City; the gangue particles or powders are preferably gangue particles or powders from Boli County, Qitaihe City. The SiO2 content in the graphite tailings produced in Luobei County, Hegang City and the gangue raw materials in Boli County, Qitaihe City is between 35% and 65%, and the content ratio of SiO2 to Al2O3 is between 2-5. Specifically, the SiO2 content is 38.5% to 64.4%, the Al2O3 content is 10.9% to 22.2%, the content ratio of SiO2 to Al2O3 is about 2.9 to 3.5, the CaO content is 1.03% to 15.8%, the Fe2O3 content is about 4.1% to 17.4%, and the SO3 content is about 1.06% to 10.5%.

[0046] In the preferred embodiment of the present invention, in the alkali melting treatment described in 1), the weight ratio of the industrial solid waste to the NaOH fine powder during co-grinding is 1:0.6-2.0; the high-temperature roasting temperature is 650°C-750°C, and the roasting time is 2h-4h.

[0047] In a preferred embodiment of the present invention, in the aging treatment described in 2), the weight ratio of the solid after alkali fusion treatment to sodium silicate is 1:0.30-0.80.

[0048] In a preferred embodiment of the present invention, in the aging treatment described in 2), the liquid-to-solid ratio when adding water and stirring sufficiently is 6 to 12 mL / g.

[0049] In a preferred embodiment of the present invention, in the aging treatment described in 2), the low-temperature aging treatment includes first treating at a temperature of 50 to 80° C. for 1 h to 3 h, and then treating at room temperature for 12 h to 16 h.

[0050] In a preferred embodiment of the present invention, the hydrothermal reaction temperature in 3) is 95° C. to 110° C., and the reaction time is 7 h to 9 h.

[0051] Based on the description of the above specific implementation methods, the present invention further embodies the technical solution and technical effects of the present invention by listing examples below. However, the scope of the present invention is not limited to the specific examples listed.

[0052] Example 1. Preparation of graphite tailings-based ultrafine powder

[0053] A method for preparing a graphite tailings-based ultrafine powder comprises the following steps:

[0054] The graphite tailings after roasting (its microscopic morphology is shown in Figure 2A) and NaOH fine powder in a weight ratio of 1:1.2-1.8, grind and mix evenly, roast at 700℃-750℃ for 2h-4h, and alkali-melt to obtain a powder containing silicate and aluminate; the obtained powder is mixed with sodium silicate in a weight ratio of 1:0.45-0.70 and grind evenly, then add water at a liquid-solid ratio of 8-12mL / g and stir thoroughly, age at 70-80℃ for 1h-3h, and continue to age at room temperature for 12h-16h. Stir continuously during the aging reaction, and the stirring speed is not less than 600r / min. The aged reaction liquid is subjected to a hydrothermal reaction at 95℃-110℃ for 7h-9h in a stainless steel reactor, and after completion, it is taken out and cooled to room temperature, filtered and separated, and the water is dried to obtain a spherical ultrafine powder with a particle size of 5-10μm and good dispersibility.

[0055] The physical properties of the graphite tailings raw material used in this embodiment are significantly improved after being processed in the above steps, especially in terms of micropore area, specific surface area and particle size distribution. The specific parameter changes are shown in Table 1; the cumulative distribution of the particle size of the ultrafine powder finally obtained is shown in Table 2.

[0056] The microscopic morphology of the spherical ultrafine powder obtained in this embodiment is shown in Figure 3 ,and Figure 2A Compared with the graphite tailings raw material shown in the figure, its morphology changes from a smooth block to a small sphere with an uneven surface and scaly characteristics.

[0057] Table 1

[0058]

[0059] Table 2

[0060]

[0061] Example 2. Preparation of graphite tailings-based ultrafine powder

[0062] A method for preparing a graphite tailings-based ultrafine powder comprises the following steps:

[0063] The graphite tailings after roasting (its microscopic morphology is shown in Figure 2A) and NaOH fine powder in a weight ratio of 1:0.6-1.2, grind and mix evenly, roast at 700℃-750℃ for 2h-4h, and alkali-melt to obtain a powder containing silicate and aluminate; the obtained powder is mixed with sodium silicate in a weight ratio of 1:0.45-0.70 and grind evenly, then add water at a liquid-solid ratio of 8-12mL / g and stir thoroughly, and then age at 50-60℃ for 1h-3h, and continue to age at room temperature for 12h-16h. Stir continuously during the aging reaction, and the stirring speed is not less than 600r / min. The aged reaction liquid is subjected to a hydrothermal reaction at 95℃-110℃ for 7h-9h in a stainless steel reactor. After completion, it is taken out and cooled to room temperature, filtered and separated, and the water is dried to obtain a spherical and cubic blended ultrafine powder with a particle size of 10-15μm and good dispersibility.

[0064] The microscopic morphology of the spherical and cubic ultrafine powders obtained in this embodiment is shown in Figure 4 ,and Figure 2A Compared with the graphite tailings raw material shown in the figure, its morphology changes from a smooth block to a more dispersed granular shape with a rough surface.

[0065] Example 3. Preparation of ultrafine coal gangue-based powder

[0066] A method for preparing a gangue-based ultrafine powder comprises the following steps:

[0067] The coal gangue after roasting (its microscopic morphology is shown in Figure 2B ) and NaOH fine powder in a weight ratio of 1:1.0-1.6, grind and mix evenly, roast at 700℃-750℃ for 2h-4h, and alkali-melt to obtain a powder containing silicate and aluminate; the obtained powder is mixed with sodium silicate in a weight ratio of 1:0.30-0.45 and grind evenly, then add water at a liquid-solid ratio of 8-12mL / g and stir thoroughly, age at 70-80℃ for 1h-3h, and continue to age at room temperature for 12h-16h. Stir continuously during the aging reaction, and the stirring speed is not less than 600r / min. The aged reaction liquid is subjected to a hydrothermal reaction at 95℃-110℃ for 7h-9h in a stainless steel reactor, and after completion, it is taken out and cooled to room temperature, filtered and separated, and the water is dried to obtain a spherical ultrafine powder with a particle size of less than 1μm and good dispersibility.

[0068] The microscopic morphology of the spherical ultrafine powder with a diameter of less than 1 μm obtained in this embodiment is shown in FIG. Figure 5 ,and Figure 2B Compared with the coal gangue raw material shown in the figure, its morphology changes from a crystal with a smooth surface, irregular shape and uneven particle size to a spherical shape with smaller particles and uniform particle size.

[0069] Comparative Example 1

[0070] Preparation of gangue-based zeolite ultrafine powder, the overall method is different from Example 1 in that: the blocky gangue is crushed, sieved, dried and calcined, and the calcination temperature is 800°C and the time is 2h. The silicon-aluminum ratio of the gangue after roasting is about 4:1, and sodium aluminate is added as an aluminum source. 1.8 mol / L NaOH is added to the calcined gangue, and the liquid-solid ratio is 8. After stirring the mixture in a 65°C oil bath for 2h, it is transferred to a hydrothermal reactor and crystallized at 95°C for 10h. After the reaction is completed, it is cooled to room temperature, and then filtered and dried to obtain the gangue-based zeolite ultrafine powder, and its microscopic morphology is shown in FIG. Figure 6 The ultrafine zeolite powder in Comparative Example 1 is a tetrahedron with a smooth surface; the pore diameter is concentrated in the range of 2 to 5 nm, which is close to the average pore diameter (3.8 nm) of Example 3; the specific surface area is 13.6 m 2 / g, which is smaller than the specific surface area of ​​Example 3 (19.8m 2 / g).

[0071] Comparative Example 2

[0072] In order to maximize the role of industrial solid waste in accelerating cement hydration and improving the compressive strength and durability of composite cement materials, mechanical grinding technology is used to ultrafine the coal gangue. The method for preparing high-activity ultrafine powder based on coal gangue includes: grinding small-sized calcined coal gangue materials with a D90 particle size of 48.4μm for 30 minutes. When the grinding body size is Φ50mm and the ball mill filling rate is 30%, the maximum specific surface area is 801m 2 / kg(i.e. 0.801m 2 / g) of ultrafine powder, its microscopic morphology is shown Figure 7 The specific surface area of ​​the ultrafine powder prepared in Comparative Example 2 is much smaller than that in Example 1, and it does not show pore characteristics and regular surface structure. The particle size uniformity of the ultrafine powder is lower than that in Example 1.

Claims

1. An industrial solid waste-based ultrafine powder, which is obtained by grinding industrial solid waste particles or powder with NaOH fine powder, and then performing high-temperature roasting, grinding, low-temperature aging and hydrothermal reaction in sequence; the industrial solid waste is any one or a mixture of two of calcined and activated graphite tailings or coal gangue, and its SiO2 content is 35% to 65%, and the content ratio of SiO2 to Al2O3 is between 2-5.

2. The industrial solid waste-based ultrafine powder according to claim 1, characterized in that: More than 90% of the particles in the industrial solid waste-based ultrafine powder have a particle size of no more than 20 μm; the micropore area is no less than 30 m 2 / g; specific surface area not less than 19m 2 / g.

3. A method for preparing the industrial solid waste-based ultrafine powder according to any one of claims 1 to 2, comprising the following steps: 1) Alkali melting The fine powder of sodium hydroxide (NaOH) is mixed with the particles or powder of industrial solid waste and ground until the mixture is uniform, and then subjected to high temperature roasting treatment; The industrial solid waste is any one of calcined activated graphite tailings or coal gangue or a mixture of the two, wherein the SiO2 content is 35% to 65% and the content ratio of SiO2 to Al2O3 is between 2 and 5; The weight ratio of the sodium hydroxide fine powder to the particles or powder of industrial solid waste is 0.6 to 2.0:1; The high temperature calcination treatment has a calcination temperature of 650°C to 750°C and a calcination time of 2h to 4h; 2) Aging The solid after alkali fusion treatment in step 1) is mixed with sodium silicate in a weight ratio of 1:0.45-0.80 and ground into powder, and then water is added at a solid-liquid ratio of 6-12 mL / g, first aged at 50-80° C. for 1 h to 3 h, and then aged at room temperature for 12 h to 16 h to obtain a precursor for a hydrothermal reaction; 3) Hydrothermal reaction The precursor obtained in step 2) is subjected to a hydrothermal reaction at 95° C. to 110° C. for 7 h to 9 h, and then cooled, filtered and dried to obtain an industrial solid waste-based ultrafine powder.

4. The method according to claim 3, characterized in that: 1) The weight ratio of the sodium hydroxide fine powder to the particles or powder of industrial solid waste is 1.0-1.8:

1.

5. The method according to claim 3, characterized in that: 1) The calcination temperature of the high temperature calcination treatment is 700° C. to 750° C., and the calcination time is 2 h to 4 h.

6. The method according to claim 3, characterized in that: 1) The industrial solid waste is graphite tailings after calcination and activation, and 2) the solid after alkali fusion treatment is mixed and ground with sodium silicate in a weight ratio of 1:0.45-0.

70.

7. The method according to claim 3, characterized in that: 1) The industrial solid waste is coal gangue after calcination and activation, and 2) the solid after alkali fusion treatment is mixed and ground with sodium silicate in a weight ratio of 1:0.30-0.

45.

8. The method according to claim 3, characterized in that: 2) In the aging, water is added at a solid-to-liquid ratio of 8 to 12 mL / g, and the mixture is first aged at 70 to 80° C. for 1 h to 3 h, and then aged at room temperature for 12 h to 16 h.

9. Application of the industrial solid waste-based ultrafine powder according to any one of claims 1-2 in the preparation of low-carbon cementitious materials; the low-carbon cementitious material is an inorganic cementitious material with a three-dimensional network structure composed of AlO4 and SiO4 tetrahedral structural units, which is prepared at room temperature and pressure by replacing part of the cement with fly ash and graphite tailings under the action of an alkali activator.

10. The use according to claim 9, characterized in that: The industrial solid waste-based ultrafine powder is used as a functional additive in the preparation of the low-carbon gelling material; preferably, the industrial solid waste-based ultrafine powder is used in the preparation of the alkali-activated gelling material in an addition amount of 8-10%.